A comparative study of pain perception during the microfocused ultrasound procedure between topical anesthesia and combined topical anesthesia with forced air cooling. (27th December 2022) - Vachiramon, Vasanop; Palakornkitti, Pasita; Anuntrangsee, Tanaporn; Rutnin, Suthinee; Visessiri, Yingluck; Fabi, Sabrina
Abstract: Background: The experience of pain during microfocused ultrasound with visualization (MFU‐V) treatment is common and crucial for dictating patient satisfaction and retention. Objective: To compare the pain perception during the MFU‐V procedure between two pain reduction methods (topical anesthesia alone versus combined topical anesthesia with forced air cooling). Materials and Methods: This was a prospective, single‐blinded, randomized controlled trial. A square area on the inner side of both arms of healthy volunteers was marked as an experimental site and randomly assigned to receive each pain reduction method: topical anesthesia or combined topical anesthesia with forced air cooling. Thereafter, MFU‐V was performed with a 4.5 MHz, 4.5 mm transducer (10 lines, 0.9 J) followed by a 7 MHz, 3.0 mm transducer (10 lines, 0.3 J). The visual analog scale (VAS) for pain was measured immediately after 4.5 mm transducer (T1a), immediately after 3.0 mm transducer (T1b), and after the entire procedure (T2). Results: Twenty‐one participants with a mean (SD) age of 34.67 (±6.18) years were enrolled. The mean (±SD) pain score of combined topical anesthesia with forced air cooling‐treated area was 5.40 (±1.64), 4.80 (±1.63), and 5.40 (±1.56) at T1a, T1b, and T2, respectively. The mean pain score for topical anesthesia‐treated areas was 5.89 (±1.45), 5.00 (±1.72), and 5.76 (±1.67) at T1a, T1b, and T2, respectively. There were no statistically significant differences in the pain perception between the two methods. Conclusion: The addition of forced air cooling is not beneficial for pain reduction during the MFU‐V procedure because its temperature reduction effect cannot be delivered to the deep parts of the skin, which is the target site of MFU‐V.